Wavelet-analysis of skin temperature oscillations during local heating for revealing endothelial dysfunction - Podtaev, Sergey; Stepanov, Rodion; Smirnova, Elena; Loran, Evgenia (Microvascular research, 2015)
Skin microvessels have proven to be a model to investigate the mechanisms of vascular disease; in particular, endothelial dysfunction. To analyze skin blood flow, high-resolution thermometry can be used because low-amplitude skin temperature oscillations are caused by changes in the tone of skin vessels. The aim of our study was to test the possibilities of wavelet analysis of skin temperature (WAST) for the diagnosis of impaired regulation of microvascular tone in patients with type 2 diabetes. A local heating functional test was used for the assessment of microvascular tone regulation. A control group consisted of healthy male and female volunteers (n=5 each), aged 39.1±5.3years. A group of patients with type 2 diabetes comprised thirteen people, seven men and six women, aged 36 to 51years old (43.2±3.4years). The diagnosis of diabetes was made according to the criteria of the World Health Organization (WHO). The mean disease duration was 7.36±0.88years. Skin temperature oscillations, reflecting intrinsic myogenic activity (0.05–0.14Hz), neurogenic factors (0.02–0.05Hz) and endothelial activity (0.0095–0.02Hz) increase greatly during local heating for healthy subjects. In the group of patients with type 2 diabetes, no statistically significant differences in the amplitudes in the endothelial range were observed. Relative changes in the oscillation amplitudes in patients with type 2 diabetes were markedly lower compared to the control group. The latter indicates that the WAST method enables assessment of the state of vascular tone and the effects of mechanisms responsible for regulation of blood flow in the microvasculature. •Local heating functional test to assess the microvascular tone regulation•Wavelet analysis of skin temperature fluctuations•Oscillation for patients (type 2 diabetes) is markedly lower than for control group•Diagnostic endothelial damage before clinical manifestation of blood vessel damage